ABBM Development of Air Duct System with Damper Control - Ahmad Yusri, Muhammad Hazim; Md Nor, Mohd Hairwan; Abdul Rahman, Khairul Anuar (Research and Innovation in Technical and Vocational Education and Training, 2024)
The development of teaching aids (ABBM) for the air duct system with damper control is a product produced to facilitate the tasks of teachers and students during teaching and learning (PdP) sessions. sessions conducted in the classroom, especially for air conditioning and refrigeration. This product is produced based on the actual product on the market. However, existing products in the market have a very high cost to obtain to make them as ABBM. Therefore, this product is produced to ensure that students can learn easily by gaining hands-on experience in operating an air duct automatically. The objective of the study is to design, develop and test the functionality of air duct system products for damper control. This system is developed based on the ADDIE model which includes five phases which consist of analysis, design, development, implementation, and evaluate. This product is perfectly developed through technical analysis based on the temperature taken for each angle of the damper opening. This study has shown that the larger the opening angle of the damper, the faster the temperature drops in the testing room. This product has also been confirmed by three experts with experience in the field of refrigeration and air conditioning. The expert was given a questionnaire to obtain data in the design analysis, development and functionality of the product. Based on the results of the design analysis, All respondents agreed that the design produced is easy to understand and attractive. While for the results of the development there is a panel concerns on safety on power usage and suggest to use power supply (AC-DC) but the overall product has also done well based on the sketches made. Finally, the functionality of the product is suitable to be used as an ABBM with improvement comment to enlarge the Liquid Crystal Dispaly (LCD) user interface to make more visible and user friendly. The hope for the product produced is to be able to make this product a teaching aid to help students understand during the PdP process.